Sheep dairy and meat products: from urban consumers’ perspective to industry innovations - Martín-Collado D.; Díaz Martín C.; Serrano M.; Carabaño M.J.; Ramón M.; Zanoli R. (Innovation for sustainability in sheep and goats, 2019)
Sheep and goat production in Spain represents 8% of the final livestock production and it holds the second largest sheep population of EU-28. However, it has suffered 15 years of negative evolution of sheep numbers and sheep meat consumption. Conversely, cheese production has increased slowly but steadily during the last decade, with a sharper increase since 2012. These trends respond mainly to changes in consumption habits and consumers preferences which are highly influenced by urban way of life. In this context, four consumers’ focus groups were conducted in Madrid aiming to explore urban consumers’ awareness, attitudes and preferences towards meat and dairy sheep and goat products. Focus groups session showed that despite their high consumption of cheese, participants had an important lack of knowledge on cheese products. Participants also gave increasing importance to environmental, and animal welfare issues; however, it was globally acknowledged that price continues to be the main driver of sheep products consumption. These and other aspects are discussed in term of its implications for the design of sheep products marketing campaigns and inclusion of new goals in breeding programmes.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)